a)
d - 2 × ( 480 × 2 - 90 : 10 ) + 5 = 75
d - 2 × ( 960 - 9 ) + 5 = 75
d - 2 × 951 + 5 = 75
d - 1902 + 5 = 75
d - 1902 = 75 - 5
d - 1902 = 70
d = 70 + 1902
d = 1972
b)
100 - [ 36 + 6 × 9 - ( a : 3 + 15 ) ] : 3 = 76
100 - [ 36 + 54 - ( a : 3 + 15 ) ] : 3 = 76
100 - [ 90 - ( a : 3 + 15 ) ] : 3 = 76
[ 90 - ( a : 3 + 15 ) ] : 3 = 100 - 76
[ 90 - ( a : 3 + 15 ) ] : 3 = 24
90 - ( a : 3 + 15 ) = 24 × 3
90 - ( a : 3 + 15 ) = 72
a : 3 + 15 = 90 - 72
a : 3 + 15 = 18
a : 3 = 18 - 15
a : 3 = 3
a = 3 × 3
a = 9